THE ROLE OF MULTILINGUALISM IN INFLUENCING STUDENTS’ ENGLISH LANGUAGE ACQUISITION IN AN OUTSKIRT MALAYSIAN PRIMARY SCHOOL - Siti Norain Duka; Abdul Aziz, Azlina (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Malaysia, as a multilingual country, sets a platform for language learning. Bahasa Malaysia is a language for national unity and English is the second language and other languages as the third language. A child may speak a native language at home, speak the local national language at school and also learn at least a foreign language. The fluency of our second or third language may not be as fluent as the first language. As a result, many studies have been conducted about the learners’ mother tongue and the code-switching process. However, a study for the English teachers to overcome the influence of the mother tongue in the Iban community towards their spoken English has not been located. Therefore, a qualitative case study has been conducted in order to provide the description of case-related individuals’ and give deeper understanding on the 1) multilingual learners’ perceptions toward their English spoken language, 2) exploring multilingual influences in their spoken English and 3) To examine the influence of other languages (Bahasa Malaysia and Iban language) towards English. The participants identified are Ibans from Year 3 primary students; that is located at the outskirt primary school in Kanowit in which they are learning standard Iban language, Bahasa Malaysia and English language at school. Data were collected via semi-structured interviews, and field notes (i.e. classroom observation). The findings were structured into themes: the frequency in communicating the three languages among the three pupils at school in a day, home language support in learning, peers’ influence in communicating the English language, learners’ effort towards learning English and the mental process in learning language.